PERAN CITRA MEREK MEMEDIASI PENGARUH eWOM TERHADAP NIAT KONSUMEN MENGGUNAKAN GOPAY DI KOTA DENPASAR - Dewani, Ni Putu Risma Giri; Rastini, Ni Made (E-Jurnal Manajemen, 2021)
Purchase intention in this case the intention to use is the stage where consumers make decisions on several brands, and finally choose the alternative they like best or the process experienced by consumers in deciding which goods or services to buy based on various considerations. This research was conducted with the aim of explaining the effect of eWOM on intention to use through brand image as a mediating variable. This research was conducted on prospective GoPay users in Denpasar City with a research sample of 130 people, where the sampling technique used was purposive sampling. Collecting data using a questionnaire that is distributed online via Google form. The analysis technique used is descriptive analysis techniques and path analysis techniques and sobel test. The results of this study found that there is a positive and significant effect of eWOM on brand image, positive and significant influence of eWOM on intention to use, positive and significant influence of brand image on intention to use, and brand image positively and significantly mediates the effect of eWOM on intention to use. The implication of this research is expected to be able to provide input to GoPay management so that it can formulate the right strategy in order to maintain its existence in the future. Keywords: brand image, E-WOM, purchase intention .